Optimizing the oxygen balance by changing the A-site cations in molecular perovskite high-energetic materials - Chen, Shao-Li; Shang, Yu; He, Chun-Ting; Sun, Lin-Ying; Ye, Zi-Ming; Zhang, Wei-Xiong; Chen, Xiao-Ming (CrystEngComm, 2018)
We presented two new members of molecular perovskite high-energetic materials, (H 2 pz)[Na(ClO 4 ) 3 ] (PAP-1) and (H 2 dabco-O)[K(ClO 4 ) 3 ] (DAP-O2), in which H 2 pz 2+ (piperazine-1,4-diium) and H 2 dabco-O 2+ (1-hydroxy-1,4-diazabicyclo[2.2.2]octane-1,4-diium) act as A-site fuel cations, respectively. Compared with their H 2 dabco 2+ analogues, (H 2 dabco)[M(ClO 4 ) 3 ] (H 2 dabco 2+ = 1,4-diazabicyclo[2.2.2]octane-1,4-diium, M = Na + for DAP-1 and K + for DAP-2, respectively), PAP-1 and DAP-O2 exhibit optimized oxygen balance by employing two strategies to change the A-site cations, i.e. , “trimming the C and H atoms” of H 2 dabco 2+ by using H 2 pz 2+ to form PAP-1 and adding an O atom into H 2 dabco 2+ by using H 2 dabco-O 2+ to form DAP-O2, respectively. As suggested by DFT calculations and the K–J equation, the smaller H 2 pz 2+ cation in PAP-1 gives a significantly-optimized oxygen balance from −22.0% to −3.9% and an increased crystal density from 2.02 to 2.07 g cm −3 , resulting in a better detonation performance for PAP-1. Meanwhile the larger H 2 dabco-O 2+ cation gives a slightly-optimized oxygen balance from −21.3% to −17.1% but a decreased crystal density from 2.04 to 1.98 g cm −3 , leading to a decreased detonation performance from DAP-2 to DAP-O2. This study demonstrated how to rationally choose the A-site cations in a perovskite structure for modulating the properties of molecular perovskite high-energetic materials, providing important clues for designing more advanced energetic materials for practical use.